RELIGIOUS FREEDOM vs. FREEDOM OF EXPRESSION: an analysis of the "Olmedo Bustos y otros" case in the Inter-American Court of Human Rights. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This paper intends to discuss relevant aspects of Human Rights, as well as its historical evolution perpetrated by generations, as well as an approach on the Sovereignty of States, with the scope of seeking an understanding of the famous legal debate that took place. about the case “The Last Temptation of Christ” and what made it so peculiar, at first we have reason to believe in the fact that it circumcised around the question of the origin of the international responsibility of the State. Unlike most cases, where the State's responsibility is compromised by Executive acts, in the Chilean case, it was acts of the powers, Legislative and Judiciary that manifestly violated provisions of the American Convention.Keywords: Human Rights; Laic State; Religious freedom.